Molecular and clinical predictors of improvement in progression‐free survival with maintenance PARP inhibitor therapy in women with platinum‐sensitive, recurrent ovarian cancer: A meta‐analysis. Issue 14 (19th March 2021) - Lee, Chee Khoon; Friedlander, Michael L.; Tjokrowidjaja, Angelina; Ledermann, Jonathan A.; Coleman, Robert L.; Mirza, Mansoor R.; Matulonis, Ursula A.; Pujade‐Lauraine, Eric; Bloomfield, Ralph; Goble, Sandra; Wang, Ping; Glasspool, Rosalind M.; et al.
Abstract : BACKGROUND: The authors performed a meta‐analysis to better quantify the benefit of maintenance poly(ADP‐ribose) polymerase inhibitor (PARPi) therapy to inform practice in platinum‐sensitive, recurrent, high‐grade ovarian cancer for patient subsets with the following characteristics: germline BRCA mutation ( gBRCAm ), somatic BRCA mutation ( sBRCAm ), wild‐type BRCA but homologous recombinant‐deficient (HRD), homologous recombinant‐proficient (HRP), and baseline clinical prognostic characteristics. METHODS: Randomized trials comparing a PARPi versus placebo as maintenance treatment were identified from electronic databases. Treatment estimates of progression‐free survival were pooled across trials using the inverse variance weighted method. RESULTS: Four trials included 972 patients who received a PARPi (olaparib, 31%; niraparib, 35%; or rucaparib, 34%) and 530 patients who received placebo. For patients who had germline BRCA1 mutation ( gBRCAm1 ) (N = 471), the hazard ratio (HR) was 0.29 (95% CI, 0.23‐0.37); for those who had germline BRCA2 mutation ( gBRCAm2 ) (N = 236), the HR was 0.26 (95% CI, 0.17‐0.39); and, for those who had sBRCAm (N = 123), the HR was 0.22 (95% CI, 0.12‐0.41). The treatment effect was similar between the gBRCAm and s BRCAm subsets ( P = .48). In patients who had wild‐type BRCA HRD tumors (excluding sBRCAm ; N = 309), the HR was 0.41 (95% CI, 0.31‐0.56); and, in those who had wild‐type BRCA HRP tumors (N = 346), the HR was 0.64 (95% CI, 0.49‐0.83). The relative treatment effect was greater for the BRCAm versus HRD ( P = .03), BRCAm versus HRP ( P < .00001), and HRD versus HRP ( P < .00001) subsets. There was no difference in benefit based on age, response after recent chemotherapy, and prior bevacizumab. CONCLUSIONS: In platinum‐sensitive, recurrent, high‐grade ovarian cancer, maintenance PARPi improves progression‐free survival for all patient subsets. PARPi therapy has a similar magnitude of benefit for sBRCAm and gBRCAm . Although patients with BRCAm derive the greatest benefit, the absence of a BRCAm or HRD could not be used to exclude patients from maintenance PARPi therapy. Abstract : BRCA mutation status is able to predict for the magnitude of PARP inhibitor benefit in platinum‐sensitive recurrent high‐grade ovarian tumor. However, the absence of a BRCA mutation or homologous recombinant deficiency in high‐grade ovarian tumor cannot be used to exclude patients from such therapy.